1980
DOI: 10.1212/wnl.30.12.1298
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival and neurologic status after resuscitation from out‐of‐hospital cardiac arrest

Abstract: Thirty-eight survivors from among 117 patients hospitalized after out-of-hospital cardiac arrest were evaluated approximately 3 1/2 years later. Twenty patients were living; 18 had died. Fifty-three percent had resumed independent social activities, but only 32% had returned to work. Eight of 14 patients tested were normal on limited neuropsychologic tests. Satisfactory long-term outcome was associated statistically with the patient's being awake on admission or awakening to follow simple commands within 2 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Bigler and Alfano (1988) noted that additional, generalized cognitive impairment commonly accompanied the memory deficits. Earnest et al (1980) found that the patient or family reported significant changes in the patient's personality or mental status in 12 of 20 cases still living 3 years after out-of-hospital cardiac arrest. Grosswasser et al (1989) similarly reported undefined "behavioral disturbances" in 24 of 31 cases.…”
Section: Group Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Bigler and Alfano (1988) noted that additional, generalized cognitive impairment commonly accompanied the memory deficits. Earnest et al (1980) found that the patient or family reported significant changes in the patient's personality or mental status in 12 of 20 cases still living 3 years after out-of-hospital cardiac arrest. Grosswasser et al (1989) similarly reported undefined "behavioral disturbances" in 24 of 31 cases.…”
Section: Group Studiesmentioning
confidence: 97%
“…Armengol & Moes (1986) 9 cases Bigler & Alfano (1988) 12 cases Corkin et al (1985) 3 cases Earnest et al (1980) 20 cases Finkelstein & Caronna (1978) 10 cases Grosswasser et al (1989) 31 cases Hopkins et al (1995aHopkins et al ( , 1995b 11 cases Kotila & Kajaste (1984) 10 cases Maiese et al (1988) 9 cases Roine et al (1993) 59 cases Volpe et al (1986) 6 cases Willanger et al (1970) 25 cases Wilson (1996) 18 cases Yarnell (1976) 9 cases…”
Section: Appendixmentioning
confidence: 99%
“…Lettieri 21 Longstreth 64 Bertini 67 Bedell 77 Beuret 68 Bottiger 35 Earnest 78 Gottschalk 79 Hillis 80 Martin-Castro 81 Roewer 82 Skogvoll 36 Triano 83 Arrich 33 Dimopoulou 20 Nunes 30 Eisenberger 15 Guerot 84…”
Section: Fairmentioning
confidence: 99%
“…Clinically important cognitive impairment has been reported for 20% to 50% of the cases. [5][6][7] In a previous study, our group investigated the prevalence of chronic memory impairment among OHCA survivors. Moderate or severe impairment, assessed by the Rivermead Behavioural Memory Test (RBMT), was noted in almost 40% of the individuals assessed 6 months after cardiac arrest.…”
mentioning
confidence: 99%